2015
DOI: 10.4193/rhin14.183
|View full text |Cite
|
Sign up to set email alerts
|

Current therapeutic protocols for chronic granulomatous fungal sinusitis

Abstract: Surgery followed by itraconazole or voriconazole for Stage 1 and 2 disease and voriconazole for stage 3 disease is recommended for a good outcome. Amphotericin B is not recommended as first line therapy for CGFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…15 With regard to CGIFS, Rupa et al recently published a current therapeutic protocol and reported that azole derivatives (voriconazole or itraconazole) were consistently better than amphotericin B. 2 The duration of oral voriconazole treatment is still debatable; typically, it ranges from 6 to 18 months. 16,17 In the literature, topical antifungal application has no clear role as an adjuvant mode of therapy in CGIFS cases.…”
Section: Medical and Surgical Treatment Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 With regard to CGIFS, Rupa et al recently published a current therapeutic protocol and reported that azole derivatives (voriconazole or itraconazole) were consistently better than amphotericin B. 2 The duration of oral voriconazole treatment is still debatable; typically, it ranges from 6 to 18 months. 16,17 In the literature, topical antifungal application has no clear role as an adjuvant mode of therapy in CGIFS cases.…”
Section: Medical and Surgical Treatment Modalitiesmentioning
confidence: 99%
“…[16][17][18] Recently, Rupa et al have suggested a protocol for CGIFS management based on a staging system using clinical features and radiological findings of the disease extent. 2 In stage 1, the disease is confined to the nose and the PNSs. In stage 2, it extends to the orbit, the palate, or the oral cavity.…”
Section: Medical and Surgical Treatment Modalitiesmentioning
confidence: 99%
“…CGIFS is a rare condition, and, consequently, there is a lack of a management consensus in the literature, 4 although it is generally accepted that any treatment should involve a combination of surgery and antifungal treatment at a minimum. One recent CGIFRS case report proposed a management approach that involves a combination “conservative” surgery and long-term oral antifungals.…”
Section: Discussionmentioning
confidence: 99%
“…3 CGIFRS poses a significant diagnostic and management challenge for the clinician due to its rarity, unclear pathogenesis, and the lack of agreed management protocols. 4 …”
mentioning
confidence: 99%
“…bone, mucous membrane and vessels. Treatment is generally a combination of antifungal chemotherapy and surgery. New antifungal agents like voriconazole are more effective and reduce the need for extensive surgery; however, the duration of antifungal chemotherapy is debatable as only a few cases have been reported.…”
Section: Discussionmentioning
confidence: 99%